Kajian Literatur: Melestarikan Kembali Olahraga dan Permainan Tradisional Aceh Sebagai Metode Pendidikan Karakter Peserta Didik di Era Digital - Maspupah, Lulu; Riski Wulandari, Noor Aisah; Riani , Dini (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
This study aims to investigate the potential of traditional Acehnese sports and games as a method for character development in students, aligning with the Merdeka Curriculum. The findings reveal that these traditional activities embody values such as religiosity, cooperation, integrity, and independence, highly relevant to the Pancasila Student Profile. Furthermore, these activities contribute to a deeper understanding of local wisdom, enhance social skills, and promote physical and mental well-being among students. However, the younger generation's interest in this cultural heritage has been declining due to the rapid advancement of digital technology and the lack of adequate facilities and socialization. Previous studies have highlighted the importance of support from various stakeholders, including the government, schools, families, and the community, in preserving and developing traditional sports and games. Multiple strategies can be taken, such as integrating these activities into the school curriculum, developing extracurricular programs based on traditional games, promoting awareness through various media, and training teachers and facilitators to manage and develop these programs. The study concludes that traditional Acehnese sports and games hold immense potential as integrated tools for character education that align with the Merdeka Curriculum. Nevertheless, systematic and sustained efforts are needed to address existing challenges and ensure successful implementation.